2019
DOI: 10.7759/cureus.4083
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Response of Metastatic Hepatocellular Carcinoma to Treatment with Trans-arterial Radioembolization Followed by Sorafenib and Nivolumab

Abstract: Trans-arterial radioembolization (TARE) with Y-90 microspheres is an endovascular, liver-directed therapy suitable for treatment of locally advanced hepatocellular carcinoma (HCC) often as a way to reduce tumor size and bridge patients to resection or liver transplant. Opdivo®, or nivolumab, a programmed cell death protein 1 (PD-1) inhibitor, is an immunotherapeutic drug approved in September 2017 for the treatment of HCC in patients who have received prior sorafenib. We report on a patient with hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In theory, LDTs could lead to higher neoantigen presentation and be a stimulus to immune response. Clinical success stories when adding anti-PD-1 to LDT like Y90 [106,107] and TACE have only amounted to case reports to the best of our knowledge. Clinical trials are warranted to explore how LDT may influence the response to immunotherapeutic agents.…”
Section: Role Liver Directed Therapies Associated With Immunotherapymentioning
confidence: 99%
“…In theory, LDTs could lead to higher neoantigen presentation and be a stimulus to immune response. Clinical success stories when adding anti-PD-1 to LDT like Y90 [106,107] and TACE have only amounted to case reports to the best of our knowledge. Clinical trials are warranted to explore how LDT may influence the response to immunotherapeutic agents.…”
Section: Role Liver Directed Therapies Associated With Immunotherapymentioning
confidence: 99%
“…Similar to the 2014 phase I trial mentioned above, the 2018 SORAfenib in combination with local MICro-therapy guided by gadolinium-EOB-DTPA-enhanced MRI (SORAMIC) trial was a phase II study and evaluated sorafenib plus Y90 radioembolization versus sorafenib alone in 529 patients; while median OS rates were not very different, possible survival benefits were seen in patients younger than 65 as well as those without cirrhosis [2,20]. A 2019 case report from the University of Mississippi Medical Center reported a greater than one year response rate to consecutive treatment with TARE with Y90 followed by sorafenib and nivolumab in a patient with metastatic HCC on presentation [3]. This study also reported a case report describing a successful transition to partial hepatectomy from advanced HCC with combination Y90 radioembolization and nivolumab [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear overall survival (OS) trends have been shown in comparison to targeted treatments. Several emerging case reports may demonstrate benefit when combined with immunotherapy [3,4]. We highlight a case of prolonged survival in a patient who received a combination of Y90 radioembolization therapy with sorafenib, transarterial chemoembolization as well as nivolumab.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, we reported the first case of TLS developed after combination of nivolumab and sorafenib in a woman with advanced HCC which raised concern about the safety issue after a combination of systemic therapies with different mechanisms in advanced HCC. The concept of combining first- or second-line therapies in advanced HCC has not yet been mentioned in the guidelines, and only one case report has been published regarding the synergistic efficacy of transarterial radioembolization, sorafenib, and nivolumab [ 14 ]. Treatment response due to immunotherapy is often delayed and improved only in overall survival.…”
Section: Discussionmentioning
confidence: 99%